Omega-3 fatty acids are protective against paclitaxel-induced peripheral neuropathy: A randomized double-blind placebo controlled trial - Ghoreishi, Zohreh (BioMed Central, 2012)
BACKGROUND: Axonal sensory peripheral neuropathy is the major dose-limiting side effect of paclitaxel.Omega-3 fatty acids have beneficial effects on neurological disorders from their effects on neurons cells and inhibition of the formation of proinflammatory cytokines involved in peripheral neuropathy. METHODS: This study was a randomized double blind placebo controlled trial to investigate the efficacy of omega-3 fatty acids in reducing incidence and severity of paclitaxel-induced peripheral neuropathy (PIPN). Eligible patients with breast cancer randomly assigned to take omega-3 fatty acid pearls, 640 mg t.i.d during chemotherapy with paclitaxel and one month after the end of the treatment or placebo. Clinical and electrophysiological studies were performed before the onset of chemotherapy and one month after cessation of therapy to evaluate PIPN based on "reduced Total Neuropathy Score". RESULTS: Twenty one patients (70%) of the group taking omega-3 fatty acid supplement (n = 30) did not develop PN while it was 40.7%( 11 patients) in the placebo group(n = 27). A significant difference was seen in PN incidence (OR = 0.3, .95% CI = (0.10-0.88), p = 0.029). There was a non-significant trend for differences of PIPN severity between the two study groups but the frequencies of PN in all scoring categories were higher in the placebo group (0.95% CI = (−2.06 -0.02), p = 0.054). CONCLUSIONS: Omega-3 fatty acids may be an efficient neuroprotective agent for prophylaxis against PIPN. Patients with breast cancer have a longer disease free survival rate with the aid of therapeutical agents. Finding a way to solve the disabling effects of PIPN would significantly improve the patients’ quality of life. TRIAL REGISTRATION: This trial was registered at ClinicalTrials.gov (NCT01049295)